Analysis of eco-friendly preference and consumer satisfaction on the attributes of rice in Toboali Bangka Selatan - Yulia, Yulia; Bahtera, Novyandra Ilham; Sitorus, Rostiar; Asista, Aruna (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2024)
Rice serves as the main dietary staple for most Indonesians. The preference of environmentally conscious consumers reflects their liking or disliking of the different types of rice available. Satisfaction, in this context, refers to consumers' evaluations of their expectations when purchasing and consuming rice. It involves comparing their level of satisfaction with the actual performance of the rice after consumption. The study aims to analyze the eco-friendly preference and consumer satisfaction with the attributes of rice in Toboali Bangka Selatan. Convenience sampling was applied to collect the respondents of the study. Convenience Sampling was the technique where the sampling was conducted on consumers who were currently at home and willing to fill out the provided questionnaire. Surveys conducted through direct personal interactionTop of Form, observation, and focus group discussion were employed as the data collection technique. Importance-performance analysis (IPA) and customer satisfaction index (CSI) were used in processing the data. The study revealed that the eco-friendly preference and the quality of the eco-friendly rice had a positive impact on total consumer satisfaction which was fulfilled by the attributes of rice with 69 %. The rest such as price, taste, and ease of access were not satisfied as the important attributes were not well performed. Furthermore, the CSI score illustrated that the satisfaction of eco-friendly consumers in all classes was at the “satisfied” status.